Pandemic and Financial Performance: Pre and During Pandemic Effect of Covid-19 on Financial Performance of Pension Funds Defined Benefit Plans and Defined Contribution Plans - Andi Reski Almaida Daeng Macenning; Meyjerd Rombebunga; Poltak Simanullang (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Assessment of the financial performance of a pension fund can be done by analyzing the pension fund's financial reports. Based on the program, employer pension funds (EPF) are divided into two types, namely Defined Benefit Plan (DBP) and Defined Contribution Plan (DCP). This research aims to assess the financial performance of the Defined Benefit Plan (DBP) pension fund industry when compared with Defined Contribution Plan (DCP) pension funds pre-pandemic and during-pandemic for each financial ratio. Research was conducted on Pension Funds in Indonesia as a whole for the period January 2018 – December 2021. The ratios used to test the performance of each group of pension funds are Return on Assets (ROA), Return on Investment (ROI), Operational Cost Efficiency (EBO), Investment Cost Efficiency (EBI) and Pension Fund Growth (PDP). By using the Shapiro-Wilk W Test, Paired t Test, and Wilcoxon Signed Rank Test, the test results show that in DBP-EPF there are significant differences between pre-pandemic and during-pandemic for ROI and ROA. Where the ROI and ROA performance values pre-pandemic were higher than during-pandemic. There are no significant differences between EBO, EBI and PDP between pre-pandemic and during-pandemic in the DBP-EPF. Meanwhile, in the DCP-EPF there were no significant differences between pre-pandemic and during-pandemic for all variables. This proves that DBP-EPF experienced significant shocks during-pandemic. DBP-EPF is anticipating a strategy by reducing asset allocation to equity investment instruments, resulting in returns received that are not as good pre-pandemic